Quality parameters and oxidative stability of lamb during ageing - Zahija, Iva (Array, 2020)
The aim was to determine the quality parameters and oxidative stability of colour, lipids and proteins (formation of carbonyls) of vacuum packed lamb at a constant temperature of 2 °C ±1 °C up to 15 days post mortem. The suitability of lamb loin (longissimus lumborum) for ageing and optimal ageing period to obtain optimum sensory properties, especially tenderness and aroma was determined. A sample of 100 g lamb meat contains 23.48 g protein, 69.66 g water and 5.48 g fat. Lamb samples were the most tender after 11 days (both, sensory assessed and instrumentally measured – share force decreased by 61%) and had the best aroma after 15 days post mortem. In the meantime, the lamb became significantly brighter and more saturated (higher L*, a* and b* values), the content of secondary lipid oxidation products increased (1.7 times higher amount of malondialdehyde), and the content of protein carbonyls decreased to the initial value, despite an initial increase observed 11 days post mortem. We found that lamb loin is suitable piece for ageing; the optimal duration of ageing of loins is 15 days post mortem.